Pengaruh Motivasi Kerja dan Kinerja Guru Terhadap Peningkatan Mutu Pendidikan - Fatmawati; Supardi; Atang Suryana (PT FORMOSA CENDEKIA GLOBAL, 2022)
Among the many factors that determine the quality of education are work motivation and teacher performance. Because the teacher is the implementer of education that is very necessary. However, it is not uncommon to find teachers who lack passion in carrying out their duties, both in terms of planning lessons, implementing learning, and evaluating learning, which of course will have an impact on the success of the goals to be achieved. Work motivation and good teacher performance will certainly encourage the achievement of quality education. This study aims to determine; (1) The direct effect of work motivation on improving the quality of education, (2) The direct effect of teacher performance on improving the quality of education, (3) The direct effect of work motivation on teacher performance, (4) Indirect effect of work motivation through teacher performance on improving the quality of education. The research method used is quantitative research with correlational survey research techniques. The analytical technique used in this research is Path Analysis. While the object of this research is the entire board of teachers at private Madrasah Tsanawiyah in Ciruas District, Serang Regency. The sample of this study were 67 teachers. The results of this study prove that: (1) there is a significant direct effect of work motivation on improving the quality of education as indicated by the path coefficient number (p31) of 0.949 (2) there is a significant direct effect of teacher performance on improving the quality of education as indicated by the number path coefficient (p32) of 0.550 (3) there is a significant direct effect of work motivation on teacher performance as indicated by the path coefficient value (p21) of 0.812 (4) there is a significant indirect effect of work motivation and teacher performance on improving the quality of education. That is, the contribution of work motivation affects the quality of education by 19.95% while the rest is 80.05%. This means that the higher the work motivation and the increase in teacher performance, the higher the quality of education will be.